TINJAUAN MAQASID AL-SYARI‘AH TERHADAP BATAS USIA PERKAWINAN DALAM HUKUM ISLAM DAN UNDANG-UNDANG PERKAWINAN INDONESIA - Suryantoro, Dwi Dasa; A. Mansur (LPPM STAI Muhammadiyah Probolinggo, 2026)
This study aims to analyze the relevance of the determination of the marriage age limit in Indonesian positive law with the principle of maqasid al-shari'ah in Islamic law. This study is motivated by the still high rate of child marriage which has an impact on poverty, low education levels, and increasing reproductive health risks. This study uses a normative legal method with a conceptual approach and a legislative approach. The analysis was carried out on Law Number 16 of 2019 concerning Marriage, classical fiqh literature, and the thought of contemporary scholars, by placing maqasid al-shari'ah as the main framework of analysis. The focus of the study is directed to the goals of the protection of the soul (ḥifẓ al-nafs), intellect (ḥifẓ al-'aql), heredity (ḥifẓ al-nasl), and property (ḥifẓ al-mal). The original contribution of this research lies in the argument that the setting of the minimum age of marriage of 19 years is a form of ijtihad jama'i based on maqasid al-shari'ah, not solely state administrative policy. The results of the study show that this provision does not contradict Islamic teachings, but is in line with the purpose of sharia in maintaining the welfare of the family and protecting the younger generation. Thus, this study emphasizes the importance of harmonization between Islamic law and positive Indonesian law through a contextual and benefit-oriented approach to maqasid al-shari'ah.